Community Health Nursing in Iran: A Review of Challenges and Solutions (An Integrative Review) - Aazam Hosseinnejad; Maryam Rassouli; Simin Jahani; Nasrin Elahi; Shahram Molavynejad (Frontiers Media S.A., 2022)
Background and ObjectiveIn recent decades, nursing has witnessed many changes in Iran. Despite the numerous advances in nursing, the health system faces many challenges in community health nursing. This study aims to review the challenges in community health nursing in Iran and provide an evidence-based solution as well.Materials and MethodsThis article is an integrated review of the literature regarding the challenges in community health nursing published between 2000 and 2021 in the databases Scopus, Medline, Cochrane Database of Systematic Reviews, Science Direct, Google Scholar, Scientific Information Database (SID). After performing searches, 20 articles were selected and studied. Data analysis was done using Russell approach (2005).FindingsThe results of this study were summarized in 6 themes consisting of challenges in community health nursing education, practical challenges in community health nursing, policy-making challenges in community health nursing, management challenges in community health nursing, and infrastructural and cultural challenges. Solutions were also proposed to address each of the above issue.ConclusionsThe results of the study showed that diverse challenges exist in community health nursing in Iran, considering that community health nurses play an important role in providing primary health care and community-based care. In order to solve these challenges, the authors have some recommendations: modifying the structure of the health system with the aim of moving toward a community-oriented approach from a treatment-oriented one, developing laws to support community health nurses, creating an organizational chart for nurses at the community level, modifying nursing students' training through a community-based approach, and covering community-based services and care under insurance.